1986
DOI: 10.3146/i0095-3679-13-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Testing Peanut Seeds for Peanut Stripe Virus1

Abstract: Peanut seeds were tested by the enzyme-linked immunosorbent assay (ELISA) for peanut stripe virus without aecting their viability. A portion of cotyledon (0.02-0.05 g) was removed from the end of the seed opposite the radicle and triturated in an antigen buffer. Virus was frequently detected in extracts of cotyledons and embryos but seldom in the testa. Portions of one infected seed in ten could be detected. Correlations among ELISA, infectivity assays, and growing out tests were obtained. The ELISA technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Field experiments were conducted on the Agronomy Farm, Coastal Plain Experiment Station, in 1985 and1986 to determine the effect of PStV infection initiated at different stages of plant development on Florunner peanut. Certified Florunner seed were planted on Tifton loamy sand (fine, loamy, siliceous, thermic Plinthic Paleudults) at ca.…”
Section: Methodsmentioning
confidence: 99%
“…Field experiments were conducted on the Agronomy Farm, Coastal Plain Experiment Station, in 1985 and1986 to determine the effect of PStV infection initiated at different stages of plant development on Florunner peanut. Certified Florunner seed were planted on Tifton loamy sand (fine, loamy, siliceous, thermic Plinthic Paleudults) at ca.…”
Section: Methodsmentioning
confidence: 99%
“…This variability in infection rate is to some extent explained by the season and developmental stage of the plants at which a crop is exposed to infection. Thus, the rates of peanut/groundnut seed infection in Georgia (USA) with the BCMV strain PStV ranged from 37% in summer to 18% in winter, while it ranged from 19% to 11% in a Spanish cultivar (Demski & Warwick, 1986). Morales and Castano (1987) discovered that the incidence of seed transmission of five BCMV strains in 14 mosaic-susceptible bean cultivars is significantly affected by the inoculation date.…”
Section: Seed Transmissionmentioning
confidence: 97%
“…When seed axes from virus-infected seed were cultured on MS and MSR media, 37.5 and 56.7% of the resulting seedlings, respectively, were identified as free of PStV antigens (Table 1). Previous research demonstrated a high correlation between PStV in cotyledons and transmission to seedlings in grow-out tests (Demski and Warwick, 1986). Because some of the seed axes excised from cotyledons that were PStV -positive by ELISA gave rise to healthy seedlings, it is assumed that virus was not present in some seed axes although the viral antigens were detected in cotyledons.…”
Section: Resultsmentioning
confidence: 99%
“…After drying for 2 wk, the seeds were individually tested by direct antigen coating enzyme-linked immunosorbent assay (DAC-ELISA) (Demski and Warwick, 1986;Hobbs et al, 1987). Approximately 20 mg of cotyledonary tissue located opposite the radicle was pulverized in 1 mL of 0.05 M sodium carbonate buffer at pH 9.6.…”
Section: Methodsmentioning
confidence: 99%